LOI IMF Dalam Keputusan Menteri Perdagangan No. 402 Tahun 1997 - Astri Natalia Manurung (Dinamika Politik, 2013)
This study is a study of the influence of the LOI IMF in the decree of trade minister 402/1997. The foccuss disscusses about the conditions of IMF that influence the decree of trade minister 402/1997. This study finding there is two important things as the main influence of IMF in the decrees. The influences are as follows: first, the structural reforms as the reform of the foreign trade program in Indonesia; the second, acceptance of foreign investment and the private sector in the implementation of economic development The method used is descriptive – qualitative method which is intended to describe an event in more detail. Keywords: Policy, Political economy, New Order.